The PROSIT Cohort of Infliximab Biosimilar in IBD: A Prolonged Follow-up on the Effectiveness and Safety Across Italy. Issue 3 (18th August 2018) - Armuzzi, Alessandro; Fiorino, Gionata; Variola, Angela; Manetti, Natalia; Fries, Walter; Orlando, Ambrogio; Maconi, Giovanni; Bossa, Fabrizio; Cappello, Maria; Biancone, Livia; Cantoro, Laura; Costa, Francesco; et al.
Abstract: Background: We report a prospective, nationwide cohort evaluating the safety and effectiveness of CT-P13. Methods: A structured database was used to record serious adverse events (SAEs), clinical remission/response, inflammatory biomarkers (CRP and calprotectin), and endoscopic findings. Results: Eight hundred ten patients with inflammatory bowel disease (IBD) (452 Crohn's disease [CD]) were enrolled. Four hundred fifty-nine patients were naïve to anti-TNFα (group A), 196 had a previous exposure (group B), and the remaining 155 were switched to CT-P13 (group C). All patients were included in the safety evaluation with a mean follow-up of 345 ± 215 days and a total number of 6501 infusions. One hundred fifty-four SAEs were reported (19%), leading to cessation of the biosimilar in 103 subjects (12.7%). Infusion reactions were 71, leading to cessation of the biosimilar in 53 subjects (6.5%), being significantly more frequent in patients pre-exposed to anti-TNFα ( P = 0.017). The efficacy of therapy was calculated in 754 IBD patients, with a mean follow-up of 329 ± 202 days. Forty-eight patients had a primary failure (6.4%), and 188 (25.6%) lost response during follow-up. Six hundred twenty-eight (364 CD) and 360 IBD patients (222 CD) completed the follow-up at 6 and 12 months, respectively. At 12 months, patients without loss of response were 71%, 64%. and 82% in groups A, B, and C, respectively (log rank P = 0.01). Clinical/endoscopic scores and inflammatory biomarkers dropped significantly in CD and UC patients ( P = 0.01 and P < 0.0001) compared with baseline. Conclusions: In this large prospective cohort, no further signals of difference in safety and effectiveness of CT-P13 in IBD has been observed.